Student performance in online learning higher education: A preliminary research - Prabowo, Hartiwi; Ikhsan, Ridho Bramulya; Yuniarty, Yuniarty (Frontiers in Education, 2022)
The impact of student performance is the focus of online learning because it can determine the success of students and higher education institutions to get good ratings and public trust. This study explores comprehensively the factors that can affect the impact of student performance in online learning. An empirical model of the impact of student performance has been developed from the literature review and previous research. The test of reliability and validity of the empirical model was evaluated through linguist reviews and statistically tested with construct reliability coefficients and confirmatory factor analysis. Overall, the results of this study prove that the structural model with second-order measurements produces a good fit, while the structural model with first-order measurements shows a poor fit